A Study of Digital Expansion Strategy in App-Based Food Delivery Services: A Customer Perspective - Putri, Zahra Maharani Eka; Khoerunisa, Rifka; Setiawan, Muhamad Givari; Rizaldi, Arjuna (Universitas Komputer Indonesia, 2025)
This study analyzes ShopeeFood’s digital expansion strategies from a consumer perspective, highlighting how digital services reshape consumption in the modern era. Using a descriptive qualitative method with semi-structured interviews, supported by secondary data, the study applies SWOT, IFAS, and EFAS analyses to evaluate internal and external factors. Findings show that ShopeeFood’s strategies—promotions, user-friendly features, and ShopeePay integration enhance customer satisfaction and loyalty. SWOT and IE Matrix results place ShopeeFood in the Grow and Build quadrant, indicating strong growth potential amid threats like price competition and consumer shifts. The Strengths–Opportunities (SO) strategy—focusing on promotions, service innovation, MSME collaboration, and human resource development—is essential for competitiveness. Overall, adaptive and sustainable digital marketing strategies are crucial to sustaining customer loyalty and expanding market share in the food delivery industry